AN ETHNO-BOTANICAL STUDY OF MEDICINAL PLANTS IN NARHAR FOREST AREA (RANILO JOHAD) OF JHUNJHUNU (RAJASTHAN) (International Journal of Food and Nutritional Sciences, 2022)
Jhunjhunu district, located in the Indian state of Rajasthan, possesses a rich diversity of flora, including numerous ethno-medicinal plants. These plants have been traditionally used by the local communities for various medicinal purposes, contributing significantly to the indigenous healthcare system. This paper aims to document the ethno-medicinal plants of Jhunjhunu district, highlighting their traditional uses, medicinal properties, and conservation status. Through field surveys, interviews with local healers, and review of ethnobotanical literature, a comprehensive list of ethno-medicinal plants has been compiled. Additionally, the paper discusses the importance of conserving these plant species for sustainable healthcare practices and biodiversity conservation in the region.